2021
DOI: 10.1002/cncr.33888
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing head and neck cancer survivors' discontinuation of survivorship care

Abstract: BACKGROUND:Little is known about cancer survivors who discontinue survivorship care. The objective of this study was to characterize patients with head and neck cancer who discontinue survivorship care with their treating institution and identify factors associated with discontinuation. METHODS: This was a retrospective cohort study of patients diagnosed with head and neck cancer between January 1, 2014, and December 31, 2016, who received cancer-directed therapy at the University of Iowa Hospitals and Clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Although not statistically significant at p < 0.05, single treatment modality approached significance ( p = 0.071) as a predictor of discontinuation of care and deserves further attention in future studies. As cited above, 8 a previous study of discontinuation of care in a cohort of HNC survivors over a 3‐year period ( N = 449) found that having received a single treatment modality was significantly associated with discontinuation of care. Patients experiencing a single treatment modality may have less severe disease and fewer treatment side effects which may explain an increased likelihood of disengagement.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Although not statistically significant at p < 0.05, single treatment modality approached significance ( p = 0.071) as a predictor of discontinuation of care and deserves further attention in future studies. As cited above, 8 a previous study of discontinuation of care in a cohort of HNC survivors over a 3‐year period ( N = 449) found that having received a single treatment modality was significantly associated with discontinuation of care. Patients experiencing a single treatment modality may have less severe disease and fewer treatment side effects which may explain an increased likelihood of disengagement.…”
Section: Discussionmentioning
confidence: 73%
“… 21 To date, few studies have specifically examined factors associated with discontinuation of care in HNC. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations